Bonjour,
A = (x + 4) (2x - 3) - (x + 1) (x - 2)
A = 2x² - 3x + 8x - 12 - (x² - 2x + x - 2)
A = 2x² - 3x + 8x - 12 - x² + 2x - x + 2
A = 2x² - x² - 3x - x + 8x + 2x - 12 + 2
A = x² + 6x - 10
B = (x - 3) (x - 1) - (2x + 3) (x - 2)
B = x² - x - 3x + 3 - (2x² - 4x + 3x - 6)
B = x² - x - 3x + 3 - 2x² + 4x - 3x + 6
B = x² - 2x² - x - 3x - 3x + 4x + 3 + 6
B = - x² - 3x + 9
C = - (5 - x) (2x + 3) - (2x + 1) (3x + 6)
C = - (10x + 15 - 2x² - 6) - (6x² + 12x + 3x + 6)
C = - 10x - 15 + 2x² + 6 - 6x² - 12x - 3x - 6
C = 2x² - 6x² - 10x - 12x - 3x - 15 + 6 - 6
C = - 4x² - 19x - 15
D = (2y + 2) (5y - 2) - (5y + 1) (2y - 1)
D = 10y² - 4y + 10y - 4 - (10y² - 5y + 2y - 1)
D = 10y² - 4y + 10y - 4 - 10y² + 5y - 2y + 1
D = 10y² - 10y² - 4y - 2y + 10y + 5y - 4 + 1
D = 9y - 3